Problems of foreign indebtedness of developing countries - SEGRÉ C. (PSL Quarterly Review, 2014)
The present paper considers the difficulties of less-developed countries in meeting their heavy and growing foreign commitments on debt service account. The first aspect of this problem relates to the determination of the limits within which foreign indebtedness should be contained in developing countries. The second aspect relates the method of ensuring that, if such limits are respected, the service of the foreign debt will not, in spite of all, impose intolerable strains on the balance of payments of the capital importing country. The author first sketches the economic background of the problem of estimating the limits to foreign indebtedness. Policy aspects are then considered and in particular the setting of interest rate, amortization, and other conditions in individual lending operations in favour of developing countries. JEL: F31, F32, F34